High-dielectric mouldable and printable wax reinforced with ceramic nanofillers and its suitability for capacitive sensing. (3rd August 2021) - Brito-Pereira, Ricardo; Rodrigues-Marinho, T; Tubio, C R; Costa, P; Lanceros-Mendez, S
Abstract: Functional polymer composites are being increasingly developed to improve performance and integration into devices. Paraffin wax, as a material suitable for paper-based microfluidics, can be combined with ceramic materials to adapt its dielectric constant, an essential property for many applications, such as printed electronics. Paraffin wax reinforced with high-dielectric ceramic nanofillers such as barium titanate (BT) has been developed with varying filler content up to 50 weight percentage (wt%) and processed by moulding and screen-printing techniques, without the use of solvents. BT shows homogenous dispersion in smaller agglomerates into paraffin wax composites, with agglomerates up to 20 μ m of diameter for larger filler contents. The moulded composite wax shows a Young modulus of about 7.8 MPa in compression mode, similar to pristine wax and composites. Further, it supports forces up to 400 N under compression and strains up to 20%. Mechanical hysteresis decreases drastically for the 1st cycles, stabilizing at 30 kJ m −3 in the fifth cycle. Wax and respective composites were printed over a PET substrate and support bending deformation up to 4 mm of bending for 100 cycles. The dielectric constant of the pristine paraffin wax is about ϵ = 9, increasing up to ϵ = 18 for the composite with 50 wt% BT. Theoretical modelling of the dielectric response shows that models that consider the shape and orientation of the fillers predict in a more precise way the dielectric behaviour of the composites, being the Tinga model the one that presents a better prediction of the experimental dielectric behaviour for the BT/wax composites.